COLLECTION OF MICROBIOLOGY PRACTICAL MATERIALS FROM CONTAMINATION-CAUSING ORGANISMS IN EDUCATIONAL LABORATORIES - Kurniawati, Atik; Hariyanto, Tanto; Hupitoyo, Hupitoyo (Jurnal Pendidikan Kesehatan, 2025)
Educational laboratories often face microbiological contamination issues originating from various sources, such as equipment, air, and laboratory users. Although this contamination is typically viewed as a hindrance, contaminant microorganisms can be utilized for educational purposes. This study aims to develop a method for creating microbiological slides from contaminant organisms in educational laboratories and to evaluate their effectiveness in supporting microbiology learning. The research adopts a descriptive qualitative approach. The results revealed the identification of six species of contaminant molds successfully cultured on growth media. Microscopic analysis of the slides prepared from these molds demonstrated clear spore and hyphal structures under the microscope, making them effective teaching materials for studying fungal morphology. Conclusion: Slides derived from airborne laboratory contaminants can be utilized as teaching materials to support microbiology learning while simultaneously raising awareness about the importance of contamination control.